Responding to the Islamic state's foreign fighters : retribution or rehabilitation? - Farish A. Noor (2014)
Heated debate about the fate of foreign fighters joining the Islamic State, the jihadist group that controls a swath of Iraq and Syria, spotlights a host of societal problems in Europe. It also highlights the degree of alienation that prompts young men and women to join a brutal force and calls into question the efficacy of criminalisation.